The Effect of Dual Trigger on In Vitro Fertilization/Intracytoplasmic Sperm Injection Outcomes in Patients with Suboptimal Ovarian Response (POSEIDON Classification Group I): A Randomized Clinical Trial - Maryam Hafezi; Arezoo Arabipoor; Maryam Zareei; Samira Vesali; Parisa Mostafaei; Nadia Zameni (International Journal of Fertility and Sterility)
Background: The study was conducted to investigate the effect of dual trigger with gonadotropin-releasing hormone agonist (GnRH-a) and standard dose human chorionic gonadotropin (hCG) on in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) outcomes in patients with a history of suboptimal ovarian response.Materials and Methods: In this randomized clinical trial, 52 infertile women who were referred to Royan Institute from November 2019 to November 2022 for a second treatment with IVF/ICSI cycles, and had a suboptimal ovarian response [the Patient-Oriented Strategies Encompassing IndividualizeD Oocyte Number (POSEIDON) classification group I] in their previous cycle were evaluated. Ovulation stimulation was performed in all patients with the standard antagonist protocol. At the point of the final ovarian stimulation, patients were randomly assigned into two groups using the permuted block randomization method. In the dual trigger group, 0.2 mg of GnRH-a and two ampoules of recombinant hCG subcutaneously were administered to the patients at the same time. In control group, only two ampoules of recombinant hCG were injected subcutaneously. The ovarian stimulation outcomes and pregnancy rates were compared between groups utilizing appropriate statistical methods.Results: The two groups were homogeneous in terms of baseline characteristics. The statistical differences were found between groups in terms of, the total number of retrieved oocytes and the number of metaphase II (MII) oocytes as well as the number of obtained and frozen embryos in the dual trigger group were significantly more than those of in the control group (P=0.001, P=0.022, P=0.01, and P=0.035, respectively). The clinical pregnancy and live birth rates in the dual group were higher than those of the control group; nevertheless, the differences were not statistically significant (40.9 vs. 25% and 40.9 vs. 20%, P=0.275 and P=0.143, respectively).Conclusion: By virtue of these findings, dual trigger significantly improved the ovarian stimulation outcomes in the patients with a history of unexpected poor response. To validate the current findings, further clinical trials with larger sample sizes are required (registration number: NCT04549649).